Pemanfaatan Terapi Musik terhadap Kecemasan Ibu Hamil di Indonesia (Literature Review) - Ardelia Bertha Prastika; Fadiah Maharani; Nabilah Mukti Rifahmi; Wahyul Anis (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Pregnancy is a stressful reproductive process and increases anxiety. The prevalence of anxiety symptoms in Indonesia reaches 22.9%. One alternative therapy applied to reduce anxiety by music therapy. This literature review aims to determine the effect of music therapy on anxiety in pregnant women in Indonesia. Literature searches were carried out on Pubmed, Web of Science, Google Scholar, and Scopus with the last ten years of publication. The results of the analysis of the seven articles obtained related to the effect of music therapy on anxiety in pregnant women in Indonesia, that anxiety often occurs in primigravida pregnant women and before delivery. Anxiety is an indicator of stress and physiologically causes activation of the hypothalamus-pituitary adrenal (HPA) axis and increased activity of the sympathetic nervous system such as heart rate and blood pressure is released. Utilization of various types of music, including classical music, gamelan, and others as therapy has significant results in reducing anxiety, because the rhythm and tempo of music resembles the human heart rate, thus providing a state of rest for the body. Music intervention research found the most effective time duration, which is in the 30-minute relaxation period and is optimal in the morning, and has the best duration at 12 weeks of intervention. It can be concluded that the use of music therapy for anxiety in pregnant women in Indonesia can be used as an effective alternative to reduce anxiety for pregnant women, especially before delivery.